Analysis of Macroeconomic Variables on the Yield of Retail Sukuk SR010 in Indonesia: Analisis Variabel Makroekonomi terhadap Yield Sukuk Ritel SR010 di Indonesia - Muhammad Imam Syarifuddin (Fakultas Ekonomi Universitas Kadiri, 2024)
Indonesia is a country that has a very good growth and development of the Islamic capital market and shows a positive trend. The Islamic capital market is a muamalah product in which every transaction is guided by sharia principles. The existence of two instruments in the Islamic capital market in Indonesia, one of which is sukuk, is expected to be able to attract public interest in investing in the Islamic capital market so as to increase the government's macro economy. The purpose of this study is to discuss several macroeconomic variables that are independent variables in the study of the sr010 retail sukuk yield which is still relatively new and supported by the conditions of Indonesia which are currently growing in economic progress. The methodology used in this study is the use of secondary time series data during the period Januati 2015 to December 2019 with the object of the volume of issuance of retail sukuk sr010. The results of this study indicate that the independent variables are not in accordance with the hypothesis, which means that all independent variables used are less able to influence the value of the sukuk yield on the sr010 retail sukuk